CORPORATE SOCIAL RESPONSIBILITY, PURCHASE INTENTION DAN CORPORATE IMAGE PADA RESTORAN DI SURABAYA DARI PERSPEKTIF PELANGGAN - Hatane Semuel; Elianto Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2008)
This research is done to find out the implementation of Corporate Social Responsibility (CSR) towards purchase intention in some restaurants in Surabaya by using corporate image as an intervening variable. There are 105 respondents who become the customers of some restaurants implementing CSR. CSR is viewed from triple bottom line dimensions, which are economic dimension, social dimension, and environmental dimension. The research shows that Corporate Social Responsibility (CSR) has direct influence on purchase intention as well as corporate impage; whereas corporate image has influenced directly on purchase intention. In this case corporate image serves as an intervening variable between Corporate Social Responsibility and purchase intention.